Neferine inhibits the growth of human osteosarcoma cells through activating P38/JNK and suppressing Wnt/β-catenin signaling pathway - Jingtao Xu; Xiaoxuan Wang; Lijuan Luo; Haichao Xia; Qiuping Lu; Yanran Huang; Yuping Wang; Jun Zhang; Habu Jiwa; Runhan Zhao; Chuang Xiong; Jinyong Luo; et al. (Journal of Functional Foods, 2022)
Osteosarcoma (OS) is one of the most common types of bone malignant tumors. Clinical commonly used therapeutic drugs of OS treatment are prone to toxic and side effects, so it is supposed to develop new drugs with low toxicity and low side effects. As a Chinese traditional medicine, Neferine(C38H44N2O6) has inhibitory effects in various tumors. In the present study, we investigated the effects of Nef on OS cells in vitro and in vivo. We found that Nef inhibited cell proliferation, reduced migration, decreased invasion, and induced cell cycle arrest of OS cells. Notably, we demonstrated that Nef had no obvious effect on proliferation and apoptosis of normal cells. Besides, Nef repressed tumor growth of OS cells in xenograft mouse model. Mechanically, we found that Nef increased the phosphorylation level of P38 and JNK and suppressed Wnt/β-Catenin signaling pathway. In summary, our research validates that Nef may inhibit the proliferation, migration, and invasion of OS and promote apoptosis possibly by activating P38/JNK and suppressing Wnt/β-Catenin signaling pathway.